Branched amphiphilic polysulfides: influence of macromolecular architecture on self-assembly and oxidation responsiveness. Issue 1718 (2015) - d'Arcy, Richard; Tirelli, Nicola
ABSTRACT: 2-, 4-, 6- and 8-arm star amphiphilic block copolymers were prepared with the branching point located in the hydrophobic core composed of poly(propylene sulfide) (PPS); poly(ethylene glycol) (PEG) pendant chains completed the macromolecular structure. The level of branching influenced the rigidity of the PPS core and of the overall macromolecule, with the Mark-Houwink parameter a gradually approaching the value typical of globules for 6 and 8 arms. A binary behavior (linear vs. branched) was noticed for the kinetics of oxidation by H2 O2 and the stability of the colloidal aggregates formed in water: irrespective of the number of arms, all branched polymers showed a slower response (to oxidation) and a more stable hydrophobic domains (a critical micellar concentration < 0.01 mg/mL).